IDEOLOGI MUHAMMADIYAH - Suaidi (STIT Muhammadiyah Paciran Lamongan, 2024)
Muhammadiyah is one of the largest Islamic organizations in Indonesia which has played a significant role in the history of the development of Islam in the archipelago. Muhammadiyah's ideology is based on purifying Islamic teachings in accordance with the Al-Qur'an and Sunnah, by rejecting practices that are considered heresy, superstition and superstition. This ideology also emphasizes modernization and rationality in education, social and political matters, as well as an active role in building a society that is socially just and progress-oriented. This article aims to dig deeper into the basics of Muhammadiyah ideology, its historical development, and its impact on social and religious dynamics in Indonesia. By using a qualitative approach and historical analysis, this research finds that Muhammadiyah acts as an agent of social change that is consistent with Islamic values, but remains open to modernization and scientific progress. Muhammadiyah's ideology creates a balance between theological conservatism and social reformism, which makes this organization relevant in the Indonesian context and global challenges.